Edukasi Tuberkulosis dan Etika Batuk kepada Masyarakat Somagede, Banyumas, Jawa Tengah - Dwi Novitasari; Meli Apriyanti; Muhammad Azra Razi; Leonardo Ekarynansya Ola Belatan Koban; Meilanie Carin Latuihamallo (Yayasan Inspirasi El Burhani, 2023)
Introduction: Since 1992, the WHO has labeled tuberculosis a worldwide emergency. Delays in tuberculosis diagnosis, detection of new cases, and treatment are brought on by the COVID-19 epidemic. In Somagede Village, 20 (90,9%) of 24 TB cases were successfully treated, and there were 1 (4,5%) deaths as a result of TB therapy. Objective: This public service was carrying out these activities as a kind of health promotion in order to increase public awareness of health education regarding TB prevention and prevent the spread of the disease in Somagede. Method: This public service was implemented in three steps, including the permission granted, media disclosure, and the second stage, which is currently based on approval from the government of the Somagede and the letter of duty number UHB/KET/035/1121. At the end of the session, participants' public service actions are evaluated. On June 26, 2022, this health education promotion will take place. The household is the focus. With the aid of a leaflet, PowerPoint slides, notebook, LCDs, projectors, pointers, and speakers, health education methods can be presented through lectures, discussions, demonstrations, and redemonstrations. Result: The number of participants was 30. The execution time is approximately 1 hour, with the group members organized as moderator, presenter, notuensis, observer, documentarian, and facilitator. During the implementation of the public examination, participants actively followed the entire range of activities, properly demonstrated how to wash hands, and discussed the ethics of coughing. Conclusion: Activities are running well, and there is extensive public knowledge about TB disease.